Elimination of interharmonic currents by a FAP using the technique of compensation global - Mohamed Ali Moussa; Bachir Belmadani; Ahmed Wahid Belarbi; Rachid Taleb (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This document is a contribution to improve the quality of electrical energy in the distribution network.In this article we will present a method that allows us to clean up in a very considerable way the electrical network of both harmonics and inter harmonics provoked, basically by the ultrafast switches used when controlling a PWM inverter supplying a three-phase asynchronous motor. We notice that this method can be generalized for other loads creating inter-harmonics.This proposed method was simulated using the MATLAB/SIMULINK software and had given remarkable results (there is a considerable reduction in total harmonic distortion (THD) of source current from 29.52% to 0.82%)